Introduction to Bigdata and Relation with IoT - Deore, Anjali; ., . (International Journal of Engineering and Technology, 2018)
Big Data consist of large scale data which is complicated and diverse, so that new and different types of integration of techniques and technologies are required to uncover various hidden values from such big datasets. Big Data surrounding is used to set up and examine the diverse sorts of information. Big Data be data that is so massive in volume, so various in range or moving with excessive speed is referred to as Big Data. Acquiring and analysing Big Data be a challenging job because it consists of large dispersed file systems which must be bendy, fault tolerant and scalable. Diverse technologies used by big data application toward hold the huge quantity of data are Hadoop, Map Reduce, and so on. In this paper, firstly the description of big dataset is provided. In next section the different technologies are described which are used for managing Big Data. After that, Big Data method application and in last section we discuss the relation of Big Data and IoT as well as IoT for Big Data analytics.Â Â